Market orientation and typology of agrifood cooperatives according to competitiveness. Case-study of Spanish citrus cooperatives - Lajara-Camilleri, Natalia; Server Izquierdo, Ricardo J. (REVESCO. Revista de Estudios Cooperativos, 2015)
Globalization has intensified competition more so in markets, therefore companies have to strengthen and improve their competitive position to ensure survival. To this end, it is crucial, among other issues, to protect the interests of investors while caring for their customers. In the case of cooperatives, this situation is reflected in their internal customers (members) and their external customers (markets). The approach to activities and the strategy to deal with this duality determines the degree of market orientation. Studies related to market orientation in cooperatives are relatively scarce and have frequently been focused in federative cooperatives and very specific sectors. The Spanish citrus sector is one of the most dynamic and developed in the agricultural productive context. Its vast marketing experience both in domestic and foreign markets makes the difference in the companies that deal in this subsector. This paper analyzes the position of Spanish citrus cooperatives in relation to market orientation as well as to management and strategy factors that can be related to it. A previously validated MARKOR scale is used on a 45 cooperative sample. It also establishes a typology of citrus cooperatives based on competitive factors. It permits to deepen the knowledge that exists on this issue on social Economy organizations. The results show a high degree of relationship between innovation, manager profile and the market knowledge in relation to the degree of market orientation.